Understanding the characteristics of UX Malaysia UXD community of practice (COP): a participants‟ observation - Hussain, Azham; Hussein, Idyawati; Mahmud, Murni; Mkpojiogu, Emmanuel O.C. (Mattingley Publishing, 2019)
This study reports on the research involving the use of a participant observation approach to understand the characteristics of UX Malaysia, a community of practice for user experience design (UXD). This qualitative approach provides insight into the behaviour, characteristics and attitude of the members of the community of practice which they may not express when other research approaches are used. The results reveal deep insight about the characteristics of the observed community of practice.